On the comparative financial and risk analysis of urban development projects: the case of Athens' Hellinikon airport. (2017) - Nikoloudis, Christos; Strantzali, Eleni; Aravossis, Konstantinos
According to the literature review, the main financial approach used for investment valuation is the discounted cash flow analysis (DCFA). The financial indicators, which are calculated in the DCF Analysis, are the net present value (with net present value method - NPV) and the internal rate of return (with rate of return method - IRR), as well as the calculation of the above indicators with risk analysis (NPV-at risk, IRR-at risk). This paper outlines the DCF Analysis for comparative financial valuation of urban development projects. Motivated by the sustainable utilisation of Athens' Hellinikon airport, five alternative investing proposals for the development of the urban site were evaluated. Specifically, the NPV and the IRR of five investment proposals are calculated (using DCFA) and the cumulative probability distribution for the examined indicators has been calculated (using QRA). Important conclusions arose from the Monte Carlo simulation and the calculation of the mean values of the indicators.